Intranasal Oxytocin Lessens the Attentional Bias to Adult Negative Faces: A Double Blind within-Subject Experiment - Kim, Youl-Ri; Oh, Seung-Min; Corfield, Freya; Jeong, Da-Woon; Jang, Eun-Young; Treasure, Janet (Psychiatry investigation, 2014)
Oxytocin is a neuropeptide that is involved in social emotional processing. A leading hypothesis is that oxytocin facilitates positive prosocial behaviors; the peptide may also play a more general role in inhibiting withdrawal-related social behaviors. The present study examined these possibilities. A double-blind, placebo controlled crossover design was used with 31 healthy women. Forty-five minutes following the administration of 40 IU of intranasal oxytocin or a placebo, the participants were presented with two dot probe tests with pairs of face stimuli depicting emotional and neutral faces in adults. Oxytocin specifically reduced the attention bias toward the location of the faces of adults showing negative emotions, particularly in the case of disgust. Oxytocin did not enhance the attentional bias toward adult happy faces. The effect of oxytocin toward adult negative emotion was correlated with the sensitivity of the drive in the behavioral motivational system. Oxytocin reduces attention to negative social emotions in adults, which supports oxytocin serves to inhibit withdrawal-related social behaviour.